Low-Cost Fault Tolerant Methodology for Real Time MPSoC Based Embedded System. (19th November 2014) - Amin, Mohsin; Shakir, Muhammad; Javed, Aqib; Hassan, Muhammad; Raza, Syed Ali
Abstract : We are proposing a design methodology for a fault tolerant homogeneous MPSoC having additional design objectives that include low hardware overhead and performance. We have implemented three different FT methodologies on MPSoCs and compared them against the defined constraints. The comparison of these FT methodologies is carried out by modelling their architectures in VHDL-RTL, on Spartan 3 FPGA. The results obtained through simulations helped us to identify the most relevant scheme in terms of the given design constraints.